The Lagrange multiplier rule for super efficiency in vector optimization - Huang, H. (Journal of mathematical analysis and applications, 2008)
In this paper, we study constrained multiobjective optimization problems with objectives being closed-graph multifunctions in Banach spaces. In terms of the coderivatives and Clarke's normal cones, we establish Lagrange multiplier rules for super efficiency as necessary or sufficient optimality conditions of the above problems.